2007
DOI: 10.1016/j.apsoil.2006.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Soil nematode communities are ecologically more mature beneath late- than early-successional stage biological soil crusts

Abstract: Biological soil crusts are key mediators of carbon and nitrogen inputs for arid land soils and often represent a dominant portion of the soil surface cover in arid lands. Free-living soil nematode communities reflect their environment and have been used as biological indicators of soil condition. In this study, we test the hypothesis that nematode communities are successionally more mature beneath well-developed, late-successional stage crusts than immature, early-successional stage crusts. We identified and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 57 publications
4
45
0
1
Order By: Relevance
“…Later, surface-bound cyanobacterial colonizers are favored by the stable surface created by the filamentous cyanobacteria. These taxa are rich in sunscreen pigments and, combined with an increase in biomass, give biocrusts their common dark color, as well as the often-cited gradient from light to dark biocrusts, which indicates succession Darby et al 2007;Dojani et al 2011;Yeager et al 2004). As biocrusts darken and host more species, the ecological maturity of the microfauna also increases (Darby et al 2007).…”
Section: Successional Trajectoriesmentioning
confidence: 93%
See 1 more Smart Citation
“…Later, surface-bound cyanobacterial colonizers are favored by the stable surface created by the filamentous cyanobacteria. These taxa are rich in sunscreen pigments and, combined with an increase in biomass, give biocrusts their common dark color, as well as the often-cited gradient from light to dark biocrusts, which indicates succession Darby et al 2007;Dojani et al 2011;Yeager et al 2004). As biocrusts darken and host more species, the ecological maturity of the microfauna also increases (Darby et al 2007).…”
Section: Successional Trajectoriesmentioning
confidence: 93%
“…These taxa are rich in sunscreen pigments and, combined with an increase in biomass, give biocrusts their common dark color, as well as the often-cited gradient from light to dark biocrusts, which indicates succession Darby et al 2007;Dojani et al 2011;Yeager et al 2004). As biocrusts darken and host more species, the ecological maturity of the microfauna also increases (Darby et al 2007). In regions where succession proceeds beyond "dark" cyanobacterial crusts, typically mosses and/or lichens are reported as becoming more abundant or even dominant Kidron et al 2008;Jia et al 2008;Lan et al 2012;Lázaro et al 2008;Büdel et al 2009).…”
Section: Successional Trajectoriesmentioning
confidence: 93%
“…Presence of small mammals can, in turn, create further surface heterogeneity by creating new habitats and facilitating overall biodiversity of these mosaics (Davidson and Lightfoot, 2008). Bars and swales with abundant moss, lichen, and dark algal crusts may be potential habitats for invertebrates specialized in feeding on these resources (Belnap, 2006;Darby et al, 2007), whereas shrub zone units, which were preferentially associated with light algal crusts, may provide suitable stability for burrows used by small reptiles (Zaady and Bouskila, 2002).…”
Section: Implications Of Geomorphology and Linked Physical Land Surfamentioning
confidence: 99%
“…This shows that nematodes can find and consume various bacteria in fruit. Previous studies report that increased numbers of nematodes are found in areas of the soil that are populated with increased diversity of bacteria (Bongers, 1990;Darby et al, 2007). Our hypothesis is that diacetyl acts as a cue to allow nematodes to locate large and diverse bacterial bonanzas growing in an area where nutrients for microbial growth are abundant.…”
Section: Discussionmentioning
confidence: 81%
“…The exact reason for this is not fully known; however, rotten fruit and vegetation are a rich source of bacteria for worms to feed on. Rhabditid nematodes like C. elegans are considered enrichment-type nematodes (Bongers, 1990;Darby et al, 2007). They normally exist in a semi-hibernating dauer larval stage in nature (Barriere and Felix, 2005), but when they come upon a rich source of bacteria, the dauers will quickly grow to sexually mature adults, rapidly reproduce in very large numbers, and consume much of the bacteria present (Bongers, 1990).…”
Section: Introductionmentioning
confidence: 99%